Pengaruh Pembelajaran Pancasila terhadap Pembentukan Etika dan Moral di Kalangan Sekolah Dasar - Hikmah Ramadhani; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Pancasila learning at the elementary school level has a strategic role in forming the ethical and moral foundations of the younger generation from an early age. This article aims to analyze the influence of Pancasila learning on the formation of ethical and moral character of elementary school students with a descriptive qualitative approach. Data were obtained through classroom observations, interviews with teachers, and documentation studies in several elementary schools in urban and rural areas. The results of the study indicate that Pancasila learning that is implemented consistently and contextually can foster an attitude of tolerance, responsibility, mutual cooperation, and a sense of love for the homeland in students. Pancasila values ​​conveyed through a thematic approach and based on real experiences have proven to be more effective in forming positive student behavior in the school environment and at home. However, challenges remain, such as the lack of teacher understanding of effective learning methods and low support from the environment outside of school. Therefore, there needs to be continuous teacher training and synergy between schools, families, and communities so that Pancasila learning can function optimally in forming children's character. In conclusion, Pancasila learning has a significant influence on the formation of ethics and morals of elementary school students, but the success of its implementation is highly dependent on the method, consistency, and support from various parties. This article is expected to be a reference for educators and policy makers in designing a more adaptive and applicable value curriculum.